Urban Development and the Growth with Equity Framework: The National Football League Stadium in Downtown Los Angeles. Issue 5 (September 2019) - Saito, Leland
In political economy, research on growth coalitions and regime theory concludes that progressive coalitions representing lower-income residents and effectively working for policy change at the local level involving development are unlikely since they lack the resources necessary to build and maintain strong coalitions with long-term influence with elected officials. In Los Angeles, a coalition representing the homeless filed a lawsuit in 2012, which involved one of the most powerful developers in the region, and reached a favorable settlement. Given the strength of growth interests and factors working against redistributive policies, I ask the question, how did the coalition muster the political influence and resources necessary to compel the developer to settle the lawsuit? I contend that the settlement is evidence of a progressive coalition in the region that is working to establish a growth with equity framework and that the coalition has established political influence with local officials.